(untitled) (The Pakistan Development Review, 2001)
The phenomenon of poverty was felt and observed more during the decade of 1990s, as the overall growth slowed down. While the slowed economic growth and recessionary trends contributed to poverty, the trickle “down effect” once thought, to improve living conditions, did not reach the lowest level owing largely to lack of accessibility of institutions, unjust and non-poor policies. For these reasons, in Pakistan during the decades of 60s and 80s, when the country experienced high growth rates of 6-7 percent, 34 percent of people still lived below the poverty line. Socio-economic development, improving the quality of life in general and of rural poor in particular, welfare have been the prime stated goals of government. Therefore, rural development programmes, such as, Village-Aid, Integrated Rural Development Programme (IRDP), Peoples Works Programme, Tameer-e-watan Programme, Prime Minister’s Five Points Programme etc. were introduced to improve farm productivity, which would consequently improve incomes and quality of life of rural poor. This was done through the Department of Local Government and Rural Development. Little impact on the life of the rural poor, however, was observed partly because these were administered through closed, immutable and cloistered institutions of government which are not accessible and responsive to the needs of poor. Also, the lack of focus on community participation and need for it was evident. As these programmes were managed through government departments these lacked flexibility and out-reach. The approach of administering was fixed, rigid and lacked professionalism.